Sequential learning of emotional faces is statistical at 12 months of age. (3rd March 2022) - Mermier, Julia; Quadrelli, Ermanno; Turati, Chiara; Bulf, Hermann
Abstract: Infants are capable of extracting statistical regularities from continuous streams of elements, which helps them structuring their surrounding environment. The current study examines 12‐month‐olds' capacity to extract statistical information from a sequence of emotional faces. Using a familiarization procedure, infants were presented with videos of two actresses expressing the same facial emotion, and subsequently turning toward or away from each other. Videos displayed different emotions (i.e., anger, happiness, fear, sadness, surprise, amusement, disgust, and exasperation) and were organized sequentially, so that the transitional probabilities between videos were highly predictable in some cases, and less predictable in others. At test, infants discriminated highly predictable from low predictable transitional probabilities, suggesting that they extracted statistical regularities from the sequence of emotional faces. However, when examining the looking toward and the looking away conditions separately, infants showed evidence of statistical learning in the looking toward condition only. Together, these findings suggest that 12‐month‐old infants rely on statistical learning to segment a continuous sequence of emotional faces, although this ability can be modulated by the nature of the stimuli. The contribution of statistical learning to structure infants' social environment is discussed.